Cardiac CT Imaging Diagnosis of Cardiovascular Disease - Budoff, Matthew J.; Shinbane, Jerold S. (Springer London : Imprint: Springer, 2006)
CT has long been considered an accurate technique in the assessment of cardiac structure and function, but advances in computing power and scanning technology have resulted in its increasing popularity. It is particularly useful in evaluating the myocardium, coronary arteries, pulmonary veins, thoracic aorta, pericardium, and cardiac masses, such as thrombus of the left atrial appendage. Given this wide array of possible diagnoses and the speed at which scans can be performed, it is becoming even more attractive as an advanced, cost-effective and integral part of patient evaluation. Given this growing importance to the practising cardiologist worldwide, this book collates all relevant imaging findings of the use of cardiac CT and presents them in a clinically relevant and practical manner appropriate for residents and fellows in both cardiology and radiology. The images have been supplied by an internationally renowned set of contributing authors and represent the full spectrum of cardiac CT imaging. As ever increasing numbers of clinicians have access to cardiac CT scanners, this book provides all the relevant information to those wanting to diagnose patients using this modality.